Posttranslational Modifications Regulate the Postsynaptic Localization of PSD-95 - Vallejo, Daniela; Codocedo, Juan F.; Inestrosa, Nibaldo C. (My University, 2017)
The postsynaptic density (PSD) consists of a lattice-like array of interacting proteins that organizes and stabilizes synaptic receptors, ion channels, structural proteins, and signaling molecules required for normal synaptic transmission and synaptic function. The scaffolding and hub protein postsynaptic density protein-95 (PSD-95) is a major element of central chemical synapses and interacts with glutamate receptors, cell adhesion molecules, and cytoskeletal elements. In fact, PSD-95 can regulate basal synaptic stability as well as the activity-dependent structural plasticity of the PSD and, therefore, of the excitatory chemical synapse. Several studies have shown that PSD-95 is highly enriched at excitatory synapses and have identified multiple protein structural domains and protein-protein interactions that mediate PSD-95 function and trafficking to the postsynaptic region. PSD-95 is also a target of several signaling pathways that induce posttranslational modifications, including palmitoylation, phosphorylation, ubiquitination, nitrosylation, and neddylation; these modifications determine the synaptic stability and function of PSD-95 and thus regulate the fates of individual dendritic spines in the nervous system. In the present work, we review the posttranslational modifications that regulate the synaptic localization of PSD-95 and describe their functional consequences. We also explore the signaling pathways that induce such changes.
Keywords: psd-95; postsynaptic density; posttranslational modifications; neurodegeneration